'Come to a screeching halt': Can change in teacher education during the COVID-19 pandemic be seen as innovation?. Issue 4 (7th August 2020) - Ellis, Viv; Steadman, Sarah; Mao, Qiming
ABSTRACT: Based on interviews with a global sample of ITE leaders, this paper explores whether the changes forced on institutions and individuals as a result of the COVID-19 global pandemic can be classed as innovation. The paper goes beyond collating the various practical and organisational changes the ITE leaders made and instead focuses on the kind of changes enacted around the world and whether and how these changes can be seen as adding new value to historical ITE practices. Given the consistency of responses evident across the sample of teacher education leaders around the world, the paper concludes with a discussion of potentially global implications of the shifts in ITE practices reported and suggests that COVID-19 has indeed stimulated an innovative stance often perceived to be lacking in the sector.